2020
DOI: 10.3390/ijms21249474
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Intake and Heart Failure

Abstract: Sodium is an essential mineral and nutrient used in dietary practices across the world and is important to maintain proper blood volume and blood pressure. A high sodium diet is associated with increased expression of β—myosin heavy chain, decreased expression of α/β—myosin heavy chain, increased myocyte enhancer factor 2/nuclear factor of activated T cell transcriptional activity, and increased salt-inducible kinase 1 expression, which leads to alteration in myocardial mechanical performance. A high sodium di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 69 publications
(75 reference statements)
1
54
0
4
Order By: Relevance
“…The study’s findings are self-evident: H01, the Survival-Status was linearly correlated with SC and SS ( p < 0.05), supporting other author reports [ 12 , 13 , 14 , 42 ]. In the case of ( , , and ) refering to complications such as anemia, diabetes, and high blood pressure, SC and SS influences were not statistically significant ( p > 0.05), contradicting autor reports [ 10 , 15 ] but supporting this author report [ 42 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The study’s findings are self-evident: H01, the Survival-Status was linearly correlated with SC and SS ( p < 0.05), supporting other author reports [ 12 , 13 , 14 , 42 ]. In the case of ( , , and ) refering to complications such as anemia, diabetes, and high blood pressure, SC and SS influences were not statistically significant ( p > 0.05), contradicting autor reports [ 10 , 15 ] but supporting this author report [ 42 ].…”
Section: Discussionsupporting
confidence: 85%
“…That’s why a sodium-free diet is recommended for the general public to avoid the HF disease, and also it was found to be linked with BP and hypertension [ 10 , 11 , 12 ]. Moreover, the sodium intake significantly impacts the renin, aldosterone, noradrenaline, adrenaline, cholesterol, and triglycerides [ 13 ]. Mohammed W Akhtar et al [ 14 ] found that the renal insufficiency (abnormality in SC) in HF patients also increased five times more risk of death.…”
Section: Introduction and Related Workmentioning
confidence: 99%
“…Whereas it is often recommended that patients with chronic cardiovascular conditions follow a sodium-restricted diet, the latter often involves a poorer taste of the foods consumed, which explains the low adherence rates to a great extent [38][39][40][41]. In our study cohort, both CHF as well PAH participants consumed large amounts of sodium daily.…”
Section: Discussionmentioning
confidence: 89%
“…There is more evidence present which linking to sodium intake with BP [10], the occurrence of hypertension, [11], CVD, [12] other HF risk factors, even the latest American Heart Association guidelines for 1500 mg/d sodium tend to be sufficiently relevant for patients with stage A and B HF. Yash Patel et.al [13] have found in their review study that due to reduced renal perfusion, sodium, and water reabsorption from renal tubules, HF is characterized by sympathetic system activation and renin-angiotensin-aldosterone system (RAAS) activation. The activation of the antidiuretic and anti-natriuretic systems has been linked to a sodium-restricted diet in HF patients.…”
Section: Effect Of Abnormal Sc and Ss On Hf Patientmentioning
confidence: 99%